Ultrabroadband microwave metamaterial absorber with dielectric lossy layer - Ying Zhang; Xin Wang; Suhui Yang; Jinying Zhang; Yanze Gao; Zhuo Li (Scientific Reports)
Abstract Metamaterial absorbers exhibit high absorption and flexible tuning ability has been widely applied in energy harvesting, radiative cooling, and radar cross-section reduction. In this paper, an ultra-broadband microwave metamaterial absorber containing a lossy meta-dielectric layer was proposed. The lossy layer was a PLA meta-layer with resistive ink coating on the sidewall of the periodic structure. Through tuning the thickness and height of the resistive ink coating on the side wall, the effective impedance of the absorber was modified to match the air impedance. It could enhance the absorption in an ultrabroad microwave frequency band. Simulation results showed that over 90% absorptivity was obtained in an ultra-broad frequency range from 4.4 to 60 GHz, with a relative absorption bandwidth of 173%. Moreover, within the entire absorption band, the absorptivity was uniform, and the peak fluctuation was only 0.053. In addition, the absorber was insensitive to the wave incident angle. Even under a big oblique incident angle of 45°, the average absorptivity was still 95% and the absorption band shifted only 0.5 GHz. Detailed investigations revealed that the resistive ink coating on the PLA middle meta-layer significantly enhanced absorption within the frequency range from 20 to 60 GHz and maintained high absorption at wide incidence angles. It proved that the middle meta-layer effectively broadened the absorption band and made the absorptivity insensitive to the wave incidence angles. The experimental results of the fabricated prototype absorber effectively verified our design. We believe it has good potential in inflight vehicle stealth.